Impact of High-Temperature Heating on the Chemical Stability and Sensory Quality of Red Palm Oil - Sri Hidayati; Aulia Rahmawati; Erdi Suroso; Subeki Subeki; Tanto P. Utomo (The University of Lampung, 2025)
Red palm oil (RPO) is known for its high carotenoid content, particularly β carotene and α-carotene, which provide significant provitamin A activity. However, it is susceptible to oxidation during frying and results in nutrient loss and quality degradation. This study investigates the effects of high temperatures and prolonged heating durations on the chemical and sensory properties of RPO. The experiment involved heating RPO at three different temperatures (140°C, 180°C, and 220°C) for durations ranging from 2 to 10 hours. Chemical analysis included peroxide values, free fatty acids, and changes in functional groups through Fourier Transform Infrared (FTIR) spectroscopy. Sensory evaluations focused on aroma and color alterations due to heating. Results showed that prolonged heating of RPO at high temperatures led to significant increase in peroxide values, and the formation of oxidation products, including aldehydes and ketones, which negatively impacted the sensory qualities. The oil darkened, and a burnt aroma developed, reducing overall sensory appeal. These findings provide new insights into the optimal frying conditions to preserve the nutritional and sensory qualities of RPO, particularly by minimizing heating duration and temperature. Keywords: Nutritional value, Prolonged heating, Red palm oil, Sensory attributes, Thermal oxidation.